High-Throughput Sequence Analysis of Microbial Communities of Soybean in Northeast China - Yuanyuan Wang; Qingyao Bai; Fanqi Meng; Wei Dong; Haiyan Fan; Xiaofeng Zhu; Yuxi Duan; Lijie Chen (Agronomy)
Soybean, an essential oil crop in China, has witnessed accelerated seed transfer domestically and abroad in recent years. Seed carriage has emerged as a major route for the dissemination of soybean diseases. In this study, 14 soybean cultivars from three northeastern provinces were collected and examined for seed-borne microorganisms using traditional detection technology and high-throughput sequencing technology. Through traditional detection techniques, a total of six genera of bacteria and seventeen genera of fungi were isolated from the test varieties. The quantity and types of microorganisms on the seed surface were greater than those on the seed coat and within the seed, while the seed coat and internal seed contained fewer microorganisms. The dominant fungal genera were Cladosporium, Fusarium, Aspergillus, and Alternaria, accounting for 21.23%, 17.45%, 15.57%, and 11.56% of the genera, respectively. The dominant bacterial genera were Pseudomonas, Sphingomonas, and Pantoea, accounting for 37.46%, 17.29%, and 15.27% of the genera, respectively. The dominant genera obtained through traditional seed-carrying assay techniques were also dominant in high-throughput sequencing. However, some dominant genera obtained through high-throughput sequencing were not isolated by traditional methods. High-throughput sequencing analysis revealed that soybean seeds from Jilin Province had the highest abundance of seed-borne fungi, followed by seeds from Liaoning Province and Heilongjiang Province. Jilin Province also had the highest abundance of seed-borne bacteria, followed by Heilongjiang Province and Liaoning Province. The isolation and identification of microorganisms on soybean seeds provide a scientific basis for seed quarantine treatment and disease control, which is of great significance for soybean production in China.